The Effect of Self Control on Academic Anxiety among Guidance and Counseling Students of the 2024 and 2025 Cohorts at Universitas Jambi - Yolandari, Siti; Rahman, K.A; Yusra, Affan (The Future of Education Journal, 2026)
This study examines the effect of self-control on academic anxiety among university students, motivated by the high academic demands faced during the transition from secondary school to higher education. During this period, students are required to adapt to a new environment, heavy academic workloads, and more independent learning systems, which may lead to academic anxiety. Academic anxiety can result in decreased concentration, excessive worry, and lower academic achievement. One factor presumed to influence academic anxiety is self-control, defined as an individual’s ability to regulate behavior, thoughts, and decision-making. Effective self-control enables students to manage academic pressures more adaptively. This study employed a quantitative method with an ex post facto approach. The sample consisted of 143 students selected through simple random sampling. The instruments used included a self-control questionnaire with 27 items and an academic anxiety questionnaire with 27 items. Data were analyzed using simple regression analysis. The results showed an Asymp. Sig value of 0.200 and an R Square value of 0.137. The regression equation indicates that self-control has a significant effect on academic anxiety, meaning that higher levels of self-control are associated with lower levels of academic anxiety.